2018
DOI: 10.1097/rhu.0000000000000736
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Disease-Modifying Therapies in Rheumatoid Arthritis Is Associated With Changes in Blood Pressure

Abstract: Blood pressure may improve with treatment of RA, particularly with methotrexate or hydroxychloroquine. Leflunomide use, in contrast, is associated with increases in BP and a greater risk of incident hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 26 publications
0
24
1
2
Order By: Relevance
“…1.21-1.91)) 104 . By contrast, those patients starting methotrexate were 9% more likely to achieve an optimal blood pressure (<130/90 mmHg) after 6 months of treatment.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…1.21-1.91)) 104 . By contrast, those patients starting methotrexate were 9% more likely to achieve an optimal blood pressure (<130/90 mmHg) after 6 months of treatment.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Observational cross-sectional and prospective studies in rheumatoid arthritis have also shown that methotrexate use is associated with lower systolic and diastolic blood pressure and reduced incidence of hypertension, when compared to other DMARDs or no treatment [103][104][105][106][107][108]. In one of these studies, the associations between methotrexate treatment and lower blood pressure were also observed for 24-hr measures of peripheral and central blood pressure [103].…”
Section: Methotrexate Endothelial Function Arterial Stiffness and mentioning
confidence: 94%
“…Furthermore, treatment with leflunomide was associated with a significantly lower rate of myocardial infarction in comparison with patients with RA receiving other medications 45. In contrast to other csDMARDs, leflunomide may, however, increase blood pressure and aggravate hypertension 51…”
Section: Impact Of Medication On Development Of Heart Disease In Ramentioning
confidence: 98%